Respon Tanaman Selada (Lactuca sativa L) terhadap Aplikasi Jenis Pupuk Kandang dan Persentase Naungan: Response of Lettuce Plants (Lactuca sativa L) to Application of Manure Type and Shade Percentage - Eriesta Wahyuningtyas; Hidayat, Ramdan; Dewanti, Felisitas Deru (Agrocentrum, 2025)
In order to increase the productivity of lettuce plants on limited land, a verticulture techniques can be use. Research will start from January-February 2024 at the Urban Farming Field Laboratory, Faculty of Agriculture, National Development University "Veteran" East Java. The experimental design used was arranged in a Split Plot Design (RPT) with a Completely Randomized Design (CRD) environment. The first factor of the main plot is the percentage of shade (N) which consists of 3 treatment levels, namely: N0: No shade (control); N1 : 50% Shade; and N2: 75% Shade. The second factor as a sub plot (sub plot) is the type of manure (P) consisting of 4 treatment levels, namely: P1: Soil + Vermicompost (1:1); P2: Soil + Cow Manure (1:1); P3: Soil + Goat Manure (1:1); and P4: Soil + Chicken Manure (1:1). The combination of vermicompost with 50% shade was able to provide the highest response to the number of leaves, wet weight and canopy weight of lettuce.